THE IMPACT OF CONSTITUTIONAL OVERSIGHT ON THE SOVEREIGNTY OF PARLIAMENT (American Journal of Research in Humanities and Social Sciences, 2024)
The Constitution imposes restrictions on the political system in countries, as the authorities cannot exceed the powers specified for them and stipulated in the Constitution. All authorities must cooperate in a balanced manner to fulfill the function of the state and guarantee the rights and freedoms of individuals, without one of them interfering in or controlling the work of the other.If any authority exceeds its constitutional limits, the Constitution imposes sanctions on it within the political system. Political systems vary in their organization and types (presidential, parliamentary, representative assembly, or mixed) in determining aspects of cooperation and balance between authorities or in separating them from each other.Constitutional documents include the means to achieve these goals, which are mechanisms for mutual oversight between the legislative and executive authorities. Constitutional jurisprudence reflects this balance, and its application differs between parliamentary and presidential systems .Therefore, it is important to study the impact of constitutional review on the work of the executive and legislative authorities in Iraq. The aim of this is to shed light on the constitutional guarantees provided by the Iraqi Constitution in order to protect the constitutional text from violations, ensure non-interference in the work of the authorities based on the principle of separation of powers, and provide balance in performing the functions of each authority and thus enhance individual rights and freedoms.The study reached several resultsincluding that the role of parliamentary oversight over the executive authority varies according to the type of political system; In the presidential system, its role is weaker due to the lack of mechanisms available to it, while in the parliamentary system, its role is more effective due to the availability of the mechanisms necessary to implement it.